Improvisation of Inverter for Industrial Applications - Ranjan Mahapatra, Tapas; Chaudhary, Satis (International Journal of Psychosocial Rehabilitation, 2025)
An inverter is basically an electronic device, which converts low voltage DC power to AC electrical power of 230 volts. They are utilized for applications such as laptops, microwaves, X-ray machine, satellite systems etc. Most modern applications needs high voltage power supply and high frequency. These expanded power prerequisites have lead to noteworthy advancement in modified innovation. An inverter is an electrical device that changes over DC to AC; the converted AC can be of desired voltage and frequency with the utilization of proper transformers, exchanging control circuits. The inverter plays out the contrary operation of a rectifier.